(untitled) (Comprehensive Journal of Science, 2026)
The study aimed to demonstrate the contribution of cybersecurity in protecting systems and data at North Africa Bank in the city of Tripoli. The study relied on cybersecurity as an independent variable and the protection of systems and data as a dependent variable. A simple random sample of 97 individuals was selected, with 91 questionnaires analyzed using the SPSS program, and 6 questionnaires lost. It followed the descriptive analytical approach to interpret the relationship between the variables. It concluded that continuing to update technologies and policies periodically, along with conducting regular penetration tests, is essential to maintain this high level and ensure compliance with international standards such as PCI DSS. It recommended continuing to conduct periodic assessments of hardware and software to ensure compatibility with new technological developments and global security standards, as well as enhancing system integration through the adoption of hybrid cloud technologies and training technical teams to improve performance and protection.